Experimental and theoretical Mossbauer study of an extended family of [Fe8(μ4-O)4(μ-4-R-px)12X4] clusters. - Zueva, E; Sameera, WM; Piñero, D; Chakraborty, I; Devlin, E; Baran, P; Lebruskova, K; Sanakis, Y; McGrady, J; Raptis, R (2011)
Six [Fe(8)(μ(4)-O)(4)(μ-4-R-pyrazolato)(12)X(4)] complexes containing an identical Fe(8)(μ(4)-O)(4) core have been structurally characterized and studied by Mössbauer spectroscopy. In each case, an inner μ(4)-O bridged Fe(III) cubane core is surrounded by four trigonal bipyramidal iron centers, the two distinct sites occurring in a 1:1 ratio. The Mössbauer spectrum of each of the clusters consists of two quadrupole doublets, which, with one exception (X = NCS, R = H), overlap to give three absorption lines. The systematic variation of X and R causes significant changes in the Mössbauer spectra. A comparison with values for the same clusters computed using density functional theory allows us to establish an unequivocal assignment of these peaks in terms of a nested model for the overlapping doublets. The changes in Mössbauer parameters (both experimental and computed) for the 1-electron reduced species [Fe(8)(μ(4)-O)(4)(μ-4-Cl-pyrazolato)(12)Cl(4)](-) are consistent with a redox event that is localized within the cubane core.